Electrochemical Characterization of Nanoporous Nickel Oxide Thin Films Spray-Deposited onto Indium-Doped Tin Oxide for Solar Conversion Scopes - Muhammad Awais; Denis P. Dowling; Franco Decker; Danilo Dini (Advances in Condensed Matter Physics)
Nonstoichiometric nickel oxide (NiOx) has been deposited as thin film utilizing indium-doped tin oxide as transparent and electrically conductive substrate. Spray deposition of a suspension of NiOx nanoparticles in alcoholic medium allowed the preparation of uniform NiOx coatings. Sintering of the coatings was conducted at temperatures below 500°C for few minutes. This scalable procedure allowed the attainment of NiOx films with mesoporous morphology and reticulated structure. The electrochemical characterization showed that NiOx electrodes possess large surface area (about 1000 times larger than their geometrical area). Due to the openness of the NiOx morphology, the underlying conductive substrate can be contacted by the electrolyte and undergo redox processes within the potential range in which NiOx is electroactive. This requires careful control of the conditions of polarization in order to prevent the simultaneous occurrence of reduction/oxidation processes in both components of the multilayered electrode. The combination of the open structure with optical transparency and elevated electroactivity in organic electrolytes motivated us to analyze the potential of the spray-deposited NiOx films as semiconducting cathodes of dye-sensitized solar cells of p-type when erythrosine B was the sensitizer.